BMRHTA: Balanced Multipath Routing and Hybrid Transmission Approach for Lifecycle Maximization in WSNs - Yu, Chih-Min; Ku, Meng-Lin; Wang, Li-Chun (IEEE internet of things journal, 2022)
In this article, a balanced multipath routing and hybrid transmission approach (BMRHTA) is proposed to effectively alleviate the imbalance of the forwarding load in a sink connection area (SCA) and prolong the network lifecycle for wireless sensor networks (WSNs). To achieve the energy efficient and balanced WSNs, three design issues, including the multipath, multihop, and single-hop transmissions, are jointly optimized to maximize the overall network lifecycle. First, the path load aggregation phenomenon in the SCA, which makes the forwarding packet load unevenly distributed among hotspots, is examined. In order to achieve the load balance in SCA, multiple shortest balanced paths are generated in the BMRHTA model. In the first stage, two uncorrelated shortest paths are discovered from each node to the sink and the optimal path selection cycle can be determined to achieve the SCA load balance. Afterward, a network equilibrium policy is offered to resolve the optimal transmission period of energy balance via hybrid transmission. As a result, the balanced shortest paths, the path selection cycle and the transmission period can be determined in the network formation phase to avoid the excessive load concentration in the subsequent maintenance phase. Simulation results show that the joint two uncorrelated balanced routing and the proposed network equilibrium policy can nearly quadruple the network lifecycle extension, as compared to a conventional node power policy. Also, the proposed BMRHTA achieves better performance than the current state-of-the-art competitive approaches in terms of energy efficiency and lifecycle.